Capsaicin as an amphipathic modulator of NaV1.5 mechanosensitivity - Luke M. Cowan; Peter R. Strege; Radda Rusinova; Olaf S. Andersen; Gianrico Farrugia; Arthur Beyder (Taylor & Francis Group, 2022)
SCN5A-encoded NaV1.5 is a voltage-gated Na+ channel that drives the electrical excitability of cardiac myocytes and contributes to slow waves of the human gastrointestinal smooth muscle cells. NaV1.5 is mechanosensitive: mechanical force modulates several facets of NaV1.5's voltage-gated function, and some NaV1.5 channelopathies are associated with abnormal NaV1.5 mechanosensitivity (MS). A class of membrane-active drugs, known as amphiphiles, therapeutically target NaV1.5's voltage-gated function and produce off-target effects including alteration of MS. Amphiphiles may provide a novel option for therapeutic modulation of NaV1.5's mechanosensitive operation. To more selectively target NaV1.5 MS, we searched for a membrane-partitioning amphipathic agent that would inhibit MS with minimal closed-state inhibition of voltage-gated currents. Among the amphiphiles tested, we selected capsaicin for further study. We used two methods to assess the effects of capsaicin on NaV1.5 MS: (1) membrane suction in cell-attached macroscopic patches and (2) fluid shear stress on whole cells. We tested the effect of capsaicin on NaV1.5 MS by examining macro-patch and whole-cell Na+ current parameters with and without force. Capsaicin abolished the pressure- and shear-mediated peak current increase and acceleration; and the mechanosensitive shifts in the voltage-dependence of activation (shear) and inactivation (pressure and shear). Exploring the recovery from inactivation and use-dependent entry into inactivation, we found divergent stimulus-dependent effects that could potentiate or mitigate the effect of capsaicin, suggesting that mechanical stimuli may differentially modulate NaV1.5 MS. We conclude that selective modulation of NaV1.5 MS makes capsaicin a promising candidate for therapeutic interventions targeting MS.